2021
DOI: 10.24132/acm.2021.620
|View full text |Cite
|
Sign up to set email alerts
|

Boundary effects of a nonconcentric semipermeable sphere using Happel and Kuwabara cell models

Abstract: The effect of a closed boundary on the hydrodynamic drag of a nonconcentric semipermeable sphere in an incompressible viscous fluid is investigated. Darcy’s law holds in the permeable region and Stokes flow used inside the spherical cavity. Suitable boundary conditions are used on the surface of a semipermeable sphere and spherical cavity. Two spherical coordinate systems are used to solve the problem. By superposition principle, a general solution is constructed from the solutions based on the semipermeable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, they observed that the drag exerted on an impervious sphere is higher than the drag on a permeable sphere. Krishna Prasad [5] investigated the drag of an incompressible, viscous fluid on a noncentric, semipermeable sphere. He concluded from the article that the drag on an eccentric solid sphere is greater than that on a semipermeable sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they observed that the drag exerted on an impervious sphere is higher than the drag on a permeable sphere. Krishna Prasad [5] investigated the drag of an incompressible, viscous fluid on a noncentric, semipermeable sphere. He concluded from the article that the drag on an eccentric solid sphere is greater than that on a semipermeable sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Abbas et al, [1] discussed the boundary layer flow over a solid sphere considering the impacts of thermal radiation Prandtl number and mixed convection. The mechanism of boundary layer flow with a semipermeable sphere to describe the Happel and Kuwabara cell models through an 180 incompressible fluid has been investigated by Madasu [2]. Mohamed et al, [3] presented a dust nanoparticles model around an isothermal sphere to calculate the heat flux of nanofluids by natural convection through the bvp4c numerical technique.…”
Section: Introductionmentioning
confidence: 99%
“…She allowed different boundary conditions to be applicable at the cell surface and studied its effect on the flow. Recently, Prasad [28] worked on finding the boundary effects on an eccentric semipermeable sphere by using cell models.…”
Section: Introductionmentioning
confidence: 99%